Logos is God: A Biblical Study of John 1:1-5 - Purba, Nora; Sihombing, Salomo (Jurnal Teologi Trinity, 2024)
The Gospel of John is one of the four Gospels. It is called the Gospel because it contains news about the journey and ministry of the Lord Jesus as the living Savior. However, the Gospel of John has very different characteristics from the other Synoptic Gospels (Matthew, Mark, Luke). The influence of the Old Testament (OT) is very strong, so we suspect that the identity of Jesus is truly an inseparable part of Jewish history, so that if the Jews reject Christ, they also reject Him who is part of themselves (John 1:11). This paper attempts to elaborate on the identity of λόγος (logos) which is often the subject of theological debate. The intended effort is made through a biblical study of John 1:1-5. Therefore, the research method used in this paper focuses on the analysis of the text of John 1:1-5 in order to trace the identity of the Logos. The findings of this study show that the logos (Jesus Christ) is also God. The Son of God who revealed the Father to humans. Revelation through Jesus Christ aims to make God (the second person) known to humans.